2018
DOI: 10.1515/jisys-2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bio-Inspired Algorithm Based on Social Spiders for Improving Performance and Efficiency of Data Clustering

Abstract: Abstract Since the last decade, the collective intelligent behavior of groups of animals, birds or insects have attracted the attention of researchers. Swarm intelligence is the branch of artificial intelligence that deals with the implementation of intelligent systems by taking inspiration from the collective behavior of social insects and other societies of animals. Many meta-heuristic algorithms based on aggregative conduct of swarms through complex interactions with no supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Experimental results showed that the proposed attribute reduction algorithm is superior to existing swarmbased considering classification accuracy while confining the number of features. SSO-based algorithms were proposed for data clustering and comparisons have been made that would contribute to the literature [1,8]. Chandran et al [31] proposed the SSO algorithm for text clustering to reduce premature convergence and deal with local minima.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental results showed that the proposed attribute reduction algorithm is superior to existing swarmbased considering classification accuracy while confining the number of features. SSO-based algorithms were proposed for data clustering and comparisons have been made that would contribute to the literature [1,8]. Chandran et al [31] proposed the SSO algorithm for text clustering to reduce premature convergence and deal with local minima.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fitness characteristics of dominant males are better than non-dominant males. The offspring is produced within a particular range through mating operation between a dominant male and one or all females [1]. Each spider is demonstrated by a position in each dimension based on weight and vibrations received from the other spiders.…”
Section: Background Of Sso Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly 70% of the population is female. Each spider is characterized by its position, fitness, weight, and vibrations received from other spiders (Thalamala, Reddy & Janet, 2018). In K-centroid representation, each spider has K-centroids which are associated with a list of data instances closer to it as shown in Fig.…”
Section: Proposed Algorithm: Ssodcscmentioning
confidence: 99%